Biofilm Formation and Heat Stress Induce Pyomelanin Production in Deep-Sea Pseudoalteromonas sp. SM9913 - Zeng, Zhenshun; Cai, Xingsheng; Wang, Pengxia; Guo, Yunxue; Liu, Xiaoxiao; Li, Baiyuan; Wang, Xiaoxue (Frontiers in Microbiology, 2017)
Pseudoalteromonas is an important bacterial genus present in various marine habitats. Many strains of this genus are found to be surface colonizers on marine eukaryotes and produce a wide range of pigments. However, the exact physiological role and mechanism of pigmentation were less studied. Pseudoalteromonas sp. SM9913 (SM9913), an non-pigmented strain isolated from the deep-sea sediment, formed attached biofilm at the solid–liquid interface and pellicles at the liquid–air interface at a wide range of temperatures. Lower temperatures and lower nutrient levels promoted the formation of attached biofilm, while higher nutrient levels promoted pellicle formation of SM9913. Notably, after prolonged incubation at higher temperatures growing planktonically or at the later stage of the biofilm formation, we found that SM9913 released a brownish pigment. By comparing the protein profile at different temperatures followed by qRT-PCR, we found that the production of pigment at higher temperatures was due to the induction of melA gene which is responsible for the synthesis of homogentisic acid (HGA). The auto-oxidation of HGA can lead to the formation of pyomelanin, which has been shown in other bacteria. Fourier Transform Infrared Spectrometer analysis confirmed that the pigment produced in SM9913 was pyomelanin-like compound. Furthermore, we demonstrated that, during heat stress and during biofilm formation, the induction level of melA gene was significantly higher than that of the hmgA gene which is responsible for the degradation of HGA in the L-tyrosine catabolism pathway. Collectively, our results suggest that the production of pyomelanin of SM9913 at elevated temperatures or during biofilm formation might be one of the adaptive responses of marine bacteria to environmental cues.